1998
DOI: 10.1093/hmg/7.6.1011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal meiosis I non-disjunction of chromosome 15: dependence of the maternal age effect on level of recombination

Abstract: Non-disjoined chromosomes 15 from 115 cases of uniparental disomy (ascertained through Prader-Willi syndrome) and 13 cases of trisomy of maternal origin were densely typed for microsatellite loci spanning chromosome 15q. Of these 128 cases a total of 97 meiosis I (MI) errors, 19 meiosis II (MII) errors and 12 mitotic errors were identified. The genetic length of a map created from the MI errors was 101 cM, as compared with a maternal length of 137 cM based on CEPH controls. No significant differences were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
1
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 25 publications
7
83
1
4
Order By: Relevance
“…One study demonstrated that up to 21% of cases of maternal UPD15 show no evidence of recombination during meiosis I. 3 In our laboratory, a total of 14 cases of UPD15 were ascertained from 1998 to 2011, 11 of which were included in this study. The three cases not analyzed by CMA each showed homozygosity for at least three maternal markers; given the concordance of microsatellite markers and CMA results for all analyzed cases, we assume these three cases would be detected by CMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study demonstrated that up to 21% of cases of maternal UPD15 show no evidence of recombination during meiosis I. 3 In our laboratory, a total of 14 cases of UPD15 were ascertained from 1998 to 2011, 11 of which were included in this study. The three cases not analyzed by CMA each showed homozygosity for at least three maternal markers; given the concordance of microsatellite markers and CMA results for all analyzed cases, we assume these three cases would be detected by CMA.…”
Section: Discussionmentioning
confidence: 99%
“…176270). 2 Two well-known factors that predispose to nondisjunction are maternal age 3 and aberrant recombination 4 (e.g., lack of recombination or recombination too close to the centromere or telomere).…”
Section: Introductionmentioning
confidence: 99%
“…Threequarters of them result from maternal me1 nonsegregation events and, as for chromosome 21, are aided by a lack or a dearth of recombination. Close to 10% are of mitotic origin, 69 so that roughly one-third, or 3% of all 15 trisomies may contribute to maternal or paternal isodisomy with the implied risk of a recessive trait from a mutant. Given the high contribution of maternal meiotic nondisjunction to trisomy 15, most detected rescues will have to represent cases of maternal UPD.…”
Section: Upd Types Currently Documentedmentioning
confidence: 99%
“…[1][2][3] Approximately 70% of PWS cases are due to a paternal deletion on chromosome 15 (15q11-q13 region), 25% of PWS cases have maternal uniparental disomy (UPD) of chromosome 15 and the remaining cases result from genetic imprinting defects. [4][5][6][7][8] Much interest now revolves around the role of adipose tissue as an endocrine organ, capable of producing hormones and cytokines such as tumor necrosis factor-a, plasminogen activating inhibitor-1, leptin, interleukin-6, resistin and, more recently, adiponectin. [9][10][11][12] Adiponectin is abundant in the circulation of nondiabetic humans, but is decreased in patients with obesity, type 2 diabetes and cardiovascular disease and higher in women than in men.…”
Section: Introductionmentioning
confidence: 99%